2021
DOI: 10.18632/aging.202525
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent remodeling of gut microbiome and host serum metabolome in mice

Abstract: The interplay between microbiota and host metabolism plays an important role in health. Here, we examined the relationship between age, gut microbiome and host serum metabolites in male C57BL/6J mice. Fecal microbiome analysis of 3, 6, 18, and 28 months (M) old mice showed that the Firmicutes / Bacteroidetes ratio was highest in the 6M group; the decrease of Firmicutes in the older age groups suggests a reduced capacity of gut microflora to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 69 publications
9
32
0
Order By: Relevance
“…In this study, we examined the gut microbiota collected at 21 and 30 months of age from 22 mice and measured the aging status. Concordant with previous reports, we found that aging was associated with increased alpha diversity [ 64 ], but in our dataset this pattern was driven by the observation of higher alpha diversity in the healthy aging cohort. Consistent with previous work [ 65 ], our study also linked aging to an increase in interindividual variation in gut microbial community composition, with interindividual variation being especially high in the normal aging group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we examined the gut microbiota collected at 21 and 30 months of age from 22 mice and measured the aging status. Concordant with previous reports, we found that aging was associated with increased alpha diversity [ 64 ], but in our dataset this pattern was driven by the observation of higher alpha diversity in the healthy aging cohort. Consistent with previous work [ 65 ], our study also linked aging to an increase in interindividual variation in gut microbial community composition, with interindividual variation being especially high in the normal aging group.…”
Section: Discussionsupporting
confidence: 93%
“…Although several previous studies demonstrated the links between gut microbiota and aging in mice, these studies mainly focused on the comparison between different growth stages [ 62 , 63 , 64 ]. In this study, we examined the gut microbiota collected at 21 and 30 months of age from 22 mice and measured the aging status.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we examined the gut microbiota collected at 21 and 30 months of age from 22 mice and measured the aging status. Concordant with previous reports, we found that aging was associated with increased alpha diversity 67 . In particular, only healthy aging mice showed significantly increased Shannon diversity with age.…”
Section: ∆ F Isupporting
confidence: 93%
“…Although several previous studies demonstrated the links between gut microbiota and aging in mice, these studies mainly focused on the comparison between different growth stages [65][66][67] . In this study, we examined the gut microbiota collected at 21 and 30 months of age from 22 mice and measured the aging status.…”
Section: ∆ F Imentioning
confidence: 99%
“…Illustration created at app.biorender.com. However, studies delineating the role of gut metabolome alterations with lifespan and diseases are limited, and are only beginning to be understood (Wu et al, 2021;Zhang et al, 2021). Since, there is evidence that secretory metabolites of commensal bacteria can directly modulate SC development (Kumar et al, 2020), it would be interesting to assess how agedependent gut metabolome changes affect the oxi-inflammatory stress in the gut, and whether these changes could be correlated with increased SC burden in the intestine (Figure 4).…”
Section: Future Research Directionsmentioning
confidence: 99%